Exploring the Sources of English-Speaking Anxiety Experienced by Vocational Senior High School Students - Sinadia, Alfrits Roul; Ngingi, Yuyun Apriana (Universitas Veteran Bangun Nusantara, 2023)
This study was conducted to prove the practicality of the conceptual foundation of language anxiety observed in an English classroom. It aimed to explore the types of anxiety students experience when doing their speaking activities. Besides, it sought to explore which things cause students to feel the most anxious about speaking English. It was conducted using a qualitative phenomenological approach to describe the lived experiences of the students. The subject of research was students at a private vocational senior high school in North Minahasa, North Sulawesi. The samples consisting of five respondents were taken using a purposeful snowball sampling technique and some private interviews were conducted to take the data. The data were analyzed using three steps: data condensation, data display, and conclusion drawing. The results showed that the students experienced the fear of being laughed at by their peers when making mistakes, the fear of not making enough preparation to speak, the fear of not knowing words to use, the fear of lacking understanding of lessons explained in English, and the fear of being scolded by an English teacher due to mispronunciation. Finally, most of what causes them to experience language anxiety have to do with the fear of negative evaluation from other people.